PROGRESS IN THE FORMATION OF EFFICIENT CITIZENS: EDUCATION AND SOCIETY IN COSTA RICA IN 1930 - Agüero García, Javier (2014)
In this article, a history of education is addressed through the analysis of textbook writtenby Elias Leiva: La educación del ciudadano completo (Education of full citizen), publishedin the early 20th Century. From social perspectives, is analyzed the role of the school as acenter of education and coexistence, families in their socio-economic environment and theempowerment of citizens and national values. The author claim characterized in terms ofcreating a literate citizen, obedient of the established order and mainly, able to repudiatevices like alcoholism and Indian heritage.